Household adaptation intentions to earthquake risks in rural China. (November 2019) - Yu, Junlei; Sim, Timothy; Guo, Chunlan; Han, Ziqiang; Lau, Jocelyn; Su, Guiwu
Abstract: Earthquakes can destroy rural households' assets and livelihood in seconds and increase their vulnerability to poverty. Investigating rural residents' intentions to cope with disaster impacts is important for disaster managers and policy-makers in designing more relevant prevention and mitigation strategies. This study analyzes primary data collected in three rural villages with different landforms in Weinan city of Shaanxi province in China. The main objective is to understand the household adaptation intentions to potential earthquake risks in rural areas of China. Results revealed that household risk perception, perceived efficacy, education level and occupation played significant roles in adaptation intention to earthquake risk. However, income level and income diversity did not affect respondents' adaptation intention significantly. This study suggests that earthquake risk reduction initiatives by the government could facilitate villagers' adaptations to disaster impacts in rural China. In addition to providing disaster relief, the Chinese government could make more concerted effort to increase more financial support channels and encourage rural Chinese households, particularly villagers who live in poorer rural areas, to pro-actively invest in long-term disaster risk reduction.